PENGARUH DERAJAT DEFORMASI TERHADAP EVOLUSI STRUKTUR MIKRO DAN NILAI KEKERASAN LADAM DAN PAKU KUDA AKIBAT PROSES FORGING - Muki Satya Permana (Program Studi Teknik Mesin Universitas Tarumanagara, 2018)
This paper presents the results of advanced work as a continuation of previous observations about the identification of material and process of the horseshoe fabrication for racehorses as published in the “Jurnal Poros Vol. 15 No. 2, November 2017”. This further research is more focused on the evolution of microstructure and the value of hardness as a function of deformation degree variations of the forging process for horseshoes and horse nails. This is performed to investigate how much degree of deformation can produce form, type and phase distribution on the microstructure and the value of hardness that are relevant to the characteristics of imported products. Through this stage, the material characteristics of imported products can be approached and obtained from the local products. Thus, the quality of horseshoes and horse nails similar to imported products are expected to be able to fabricate in the local SME (Small Medium Enterprise). From the microstructure aspect, there are differences in grain shapes for Local, Australian and Swedish products because the grain forms fabricated in Sweden and Australia are more elongated than local products. This represents that the value of hardness is higher than local products except products fabricated in Australia. Local product nails have better grain because they are more equiaxial and have finer grains so that they have a high hardness value and better toughness compared to imported products. Local horseshoe show a much lower value of hardness compared to imported products. There is a peculiarity in the horseshoe because the hardness value decreases when the degree of deformation increases that is from the percentage of the work process 20% to 80%. From the microstructure of the horseshoe, the increasing deformation degree of the work process percentage 20% to 80%, the grain size is coarser and the grain size is smoother back when the percentage of the work process reaches 100%. This is proven when the percentage of the work process reaches 100%, the value of hardness increases to 147 VHN.